ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI PADA BALITA DIPUSKESMAS TAMBELAN SAMPIT PONTIANAK TIMUR TAHUN 2019 - Lubis, Ummy Athiyah; ., Ramadhaniyati; ., Winarianti (Universitas Tanjungpura, 2015)
Background: Toddler is a general term for children aged 1-3 years (toddler) and 3-5 years (preschool children). Nutritional status is a condition caused by a balance between the amount of nutritional intake and the body's nutritional needs. Purpose: To analyze the relationship between the factors that affect the nutritional status of children under five at Tambelan Health Center, Sampit, East Pontianak in 2019. Method: Quantitative with a cross sectional design, the sample technique used a simple random sampling design, with 89 samples. Retrieving data using a questionnaire and tested with Chi-Square. Result: This study shows that there is no relationship between the level of maternal knowledge with the nutritional status of toddlers with p value of 0.575 ( 0.05), the feeding pattern with the nutritional status of the p value of 0.442 ( 0.05) and parenting patterns with nutritional status. p value 0.853 ( 0.05). Conclusion: There is no relationship between the level of maternal knowledge, feeding patterns and parenting patterns with the nutritional status of weight / age for children under five. Keyword: Nutritional Status, Toddler Reference: 75 (2000-2018)